'Definitely Wrong'? The Ministry of Pensions' Treatment of Mentally Ill Great War Veterans in Interwar British and Irish Society. (January 2021) - Robinson, Michael
Shell-shock has been well examined in literary and wartime works although marginalized in post-war studies into the experience of British Army veterans of the Great War. Attention to the history of the Ministry of Pensions, the British governmental department created to provide for disabled British ex-servicemen, complicates previous criticisms of the department and its supposed inactivity in rehabilitating the mentally ill veteran. Initial attempts to treat the mentally ill veteran were progressive and innovative. However, financial stringency imposed by the British Treasury undermined the Ministry of Pensions' efforts to cure the shell-shocked veteran as did wider societal attitudes which stigmatized the mentally ill.